Hydrogen-based Autonomous Power Systems Techno-economic Analysis of the Integration of Hydrogen in Autonomous Power Systems - Zoulias, Emmanuel I.; Lymberopoulos, N.; SpringerLink (Online service) (London : Springer London, 2008)
Hydrogen-based Autonomous Power Systems analyses the introduction of hydrogen energy technologies in autonomous power systems based on renewable energy sources (RES). Autonomous applications, which are not interconnected to the main electricity grid, are expected to be a significant niche market for the early adoption of hydrogen technologies, since the cost of energy produced by conventional autonomous power systems is also currently high. Hydrogen-based Autonomous Power Systems contains a review of hydrogen technologies suitable for RES-based autonomous power systems, presents already-existing demonstration hydrogen-based power systems, and provides concrete examples for the integration of hydrogen technologies into existing autonomous power systems. Technical and economic analyses of hydrogen-based power systems are included, with illustrations and graphs, which are a useful tool for conducting pre-feasibility analyses of such power systems. Hydrogen-based Autonomous Power Systems is a valuable resource for researchers and students in the fields of hydrogen energy technologies, renewable energy power systems and distributed generation.
Autonomous Fossil Fuel and Renewable Energy (RE)- based Power Systems -- Integration of Hydrogen Energy Technologies in Autonomous Power Systems -- Review of Existing Hydrogen-based Autonomous Power Systems $1 (BCurrent Situation -- Techno-economic Analysis of Hydrogen Technologies Integration in Existing Conventional Autonomous Power Systems $1 (BCase Studies -- Market Potential of Hydrogen-based Autonomous Power Systems -- Barriers and Benefits of Hydrogen-based Autonomous Power Systems -- Roadmap to Commercialisation of Hydrogen-based Autonomous Power Systems -- Conclusions.s
Keywords: Engineering; Renewable energy resources; Energy systems; Engineering economics; Engineering economy; Power electronics; Renewable energy sources; Alternate energy sources; Green energy industries; Engineering; Renewable and Green Energy; Power Electronics, Electrical Machines and Networks; Engineering Economics, Organization, Logistics, Marketing; Energy Systems; Electronic books